International Cooperation in the field of Environmental Management and Implementation of Global Environmental Projects (Economic journal of Lesya Ukrainka Volyn National University, 2017)
The article examines the development of the global mechanisms of natural resources regulation. It displays the status of the implementation of modern resource-saving and technology-waste, as well determination by the place of strengthening mechanisms of economic cooperation of all countries in the field of ecology, the use of the positive experience of nature management and nature conservation; it analyzes the main aspects of the international ecological safety, and orientations of the world community by means of which it is possible to find effective ways of solving pressing global and regional environmental problems, areas of strengthening international cooperation in the field of environmental management.
Keywords: greening production, economic stimulus, resource saving technologies, financial security, a system of certification, market mechanisms, ecological-economic system transformation, conversion, environmental projects